The Utilization of Zoom’s Videoconferencing in Teaching English Language in Primary Stage in Riyadh: Teachers’ Perspective - Naji, Asma (Journal of Educational and Psychological Sciences, 2021)
It is expected that utilizing videoconferencing platforms in language learning and teaching differs from face-to-face education. In this regard, this study aims to examine how English teachers perceive the use of Zoom’s videoconferencing in their teaching during distance education as well as exploring skills that enhanced more and skills teachers think there were difficult to be taught online. To achieve the goal, the descriptive approach was adopted. The study sample consisted of 8 English teachers, and the questionnaire was used to collect data. The findings of this study revealed that teachers perceived Zoom as a user-friendly platform that can be used in distance education. They showed their satisfaction with their experience. The findings also discovered that speaking is the skill that was enhanced more in distance education, followed by writing, followed by listening. Even though writing was the second enhanced skill, it appeared to be the difficult skill to be taught at a distance. The study recommended the importance of holding training courses for English teachers concerning the effective strategies to be used in distance language teaching.
Keywords: videoconferencing; teaching online; distance education; EFL teachers; EFL